Rancang Bangun Sistem Penyimpanan Data Berbasis NAS dengan Raspberry Pi untuk Menunjang Kegiatan Perkuliahan di Program Vokasi Universitas Brawijaya - Primatar Kuswiradyo; Dwiki Ansarullah (Program Pendidikan Vokasi Universitas Brawijaya, 2017)
Today data storage systems vary in service, one of them is NAS. NAS is a networked storage device system that uses a special operating system to serve the needs of data files. In this applied research a data storage system based on NAS with Raspberry Pi will be made to support lectures in Vocational Program of Brawijaya University that facilitate the data exchange between lecturers and students. Built-in NAS system can be accessed via PC / laptop smartphones within the local network in the Vocational Program of Brawijaya University’s building. Keyword : Network Attached Storage , Raspberry Pi, Data Storage System